Longitudinal fitness testing - supervision of training in young alpine ski racers - Raschner, C.; Patterson, C.; Platzer, H. P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Alpine ski racing demands a multitude of technical skills and excellent physical abilities. Longitudinal systematic fitness testing and supervision of training in young alpine ski racers is one key factor in the success of the Austrian ski teams. The established norm profiles for sport motor function and fitness tests in all age groups of ski racers can help in detecting fitness deficits early. Testing over the last 10 years has shown that Austrian young ski racers (e.g. boys) have an excellent conditioning level compared to other youth athletes from different sport disciplines. Testing of training efficiency demands that the coaches continually critique and revise their programs. Coordinated off/on snow courses and optimal intergroup communications under the supervision of the Austrian Ski Federation are important frameworks for a scientific based longitudinal training process.